2002
DOI: 10.1074/jbc.m201722200
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Translation Occurs within the Core Coding Region of the Hepatitis C Viral Genome

Abstract: The majority of hepatitis C virus (HCV) isolates contain an open reading frame (ORF) overlapping with the core coding sequences in the ؉1 frame, which was assumed to be untranslated. We present evidence supporting the expression of this ORF (designated core؉1 ORF) via novel translation mechanisms. First, fusion of the luciferase gene with the HCV-1 core؉1 ORF followed by in vitro translation resulted in the synthesis of a chimeric protein (core؉1-luciferase) that exhibited ϳ54% luciferase activity relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
151
1
7

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(164 citation statements)
references
References 37 publications
5
151
1
7
Order By: Relevance
“…Moreover, HCV-1 codons 8-11 have been shown to direct both 22/11 and 21/12 programmed ribosomal frameshifting (27,28). However, our expression studies in RRL with the HCV-1a (H) isolate, in which the A-rich region is disrupted by a G and a C at the fourth and tenth positions, respectively (A AAG AAA AAC), showed that HCV-1a (H) did not produce p16 core11/F protein (18). This suggests that the efficient synthesis of core11/F protein is directly dependent on the presence of the 10As.…”
Section: Alternative Forms Of Core11 Proteins Trans-lated By Frameshimentioning
confidence: 56%
See 4 more Smart Citations
“…Moreover, HCV-1 codons 8-11 have been shown to direct both 22/11 and 21/12 programmed ribosomal frameshifting (27,28). However, our expression studies in RRL with the HCV-1a (H) isolate, in which the A-rich region is disrupted by a G and a C at the fourth and tenth positions, respectively (A AAG AAA AAC), showed that HCV-1a (H) did not produce p16 core11/F protein (18). This suggests that the efficient synthesis of core11/F protein is directly dependent on the presence of the 10As.…”
Section: Alternative Forms Of Core11 Proteins Trans-lated By Frameshimentioning
confidence: 56%
“…Since its discovery, several studies have shown that the core11/ARFP/F protein is specifically recognized by antibodies in serum (17)(18)(19)(33)(34)(35)(36)(37)(38)(39)(40) and by the memory T cells (34,36) of HCV-infected patients, providing evidence that the core11 ORF is produced during natural HCV infection in humans. However, initial studies gave variable frequencies for the detection of core11-humoral immune responses in HCV-infected individuals.…”
Section: Evidence For Core11 Protein Production During Natural Hcv Inmentioning
confidence: 99%
See 3 more Smart Citations